IDENTIFYING THE FUTURE DIRECTION OF BUSINESS UNITS TO SUPPORT EXPANSION PLAN OF PT MATAHARI PUTRA PRIMA, TBK - Andre Siswanto, Yudie; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2016)
Abstract â?? Â PT Matahari Putra Prima Tbk, or which can be shortened to PT.MPPA has four business units with many formats, consisting of, Hypermart, Foodmart, Boston Health Beauty and the last, the newest is Smart Club. Since formally established in 1986 to date, PT MPPA highly dependent sources of his income from Hypermart, considering that more than 50% of its revenue comes from Hypermart. Given Indonesia is one country with a very large number of people supported by the Indonesian population birth rate of 1.49 percent per year, and with a population that would require a lot of consumption in an effort to survive for life, on the other hand, despite economic slowdown in 2015, 2016 APRINDO optimistic in the retail industry will grow 12%, another survey of customary international survey agency, Kantar World panel Indonesia stated even though the economy is currently slow down, level of consumption or fast moving consumer goods (FMCG) still experienced a growth of 15 percent.Along with the birth rate, the prediction APRINDO, the growth rate of consumption, and investment plans by Lippo Group to expand market share, the PT MPPA should identify which business units are well worth the investment in the future to support the company's plans to become a market leader in the retail sector. The identification is done by using GE matrix - McKinsey consisting of nine areas by grouping each business based on market conditions and the strength of a business units. This tools then also used to analyze the condition of each business unit today and the identification of the future direction of each business unit which exists. From this direction it will be known that the business units which are included into the group grow and feasible for investmentÂ Keywords: Birth rate, Consumption rate, Investment, Matrix GE McKinsey